2006
DOI: 10.1080/00779954.2006.9558559
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between the share market performance and exchange rates in New Zealand: A cointegrating VAR approach

Abstract: This study employs the cointegrating VAR approach to characterise the relationships between the five exchange rates comprising the TWI and the share market in New Zealand. Weekly data covering January 1999 to June 2006 are analysed. The study discovers there are two types of long-run relationship mimicking the portfolio balance and goods market theories. That implies there is bi-directional causality in the foreign exchange and stock markets in both the short run and long run although different exchange rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
2
8
0
2
Order By: Relevance
“…The findings of the Gringer Causality Test revealed that interest rate and rate of inflation unidirectionally causes the rate of stock prices. The findings of this study are in consonance with the previous research (Chughtai, Malik, and Aftab (2015); Obben et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the Gringer Causality Test revealed that interest rate and rate of inflation unidirectionally causes the rate of stock prices. The findings of this study are in consonance with the previous research (Chughtai, Malik, and Aftab (2015); Obben et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Many other researchers also studied the causality among these variables and showed the uni and bi-directional causality among different countries, such as Mookerjee and Yu (1997) for Hong Kong, Tokyo and Singapore and Abdalla and Murinde (1997) for four Asian countries. Other studies also conducted on this relationship supported the results, such as Granger et al (2000); Smyth and Nandha (2003); Phylaktis and Ravazzolo (2005); Obben et al (2006); Yau and Nieh (2006); Pan et al (2007); Ismail and Isa (2009); Rahman and Uddin (2009); Kutty 2010 2014and Yang et al (2014). All these studies did not find a long-term relationship among the variables but there are studies that reported a long-term relationship between these two variables, such as Richards and Evans (2009); Yau and Nieh (2009); Tian and Ma (2010); Chortareas et al (2011); Harjito and McGowan (2011); Parsva and Lean (2011) and Lin (2012).…”
Section: Literature Reviewsupporting
confidence: 72%
“…(Stavarek, 2004) studies this relationship in developed economies and recent members of the European Union. Obben et al, (2006) verified this question for New Zealand stock market. (Abugri, 2008) found divergent results among Brazilian, Mexican, Argentinean and Chilean markets.…”
Section: Introductionmentioning
confidence: 75%